Development of Ethnoscience-Based Organic Chemistry Experiment e-Module: A Cane Brown Sugar Production Process in Tulungagung, Indonesia - Ali Amirul Mu'minin (Gagasan Pendidikan Indonesia, 2023)
This research aimed to develop and determine the feasibility of ethnoscience-based organic chemistry experiment e-module: a cane brown sugar production process in Tulungagung, Indonesia. This research used the research and development (R & D) method with steps according to Richey and Klein, namely Planning, Production, and Evaluation (PPE). Product feasibility tests consist of content validity tests, including materials and media, and limited trials. The average percentage score of the validity test results of materials, media, and limited trials are 86%, 86%, and 88% which shows that the ethnoscience-based organic chemistry experiment e-module: a cane brown sugar production process in Tulungagung, Indonesia is very good.